Implementasi Metode TOPSIS pada Sistem Pendukung Keputusan Penentuan Prioritas Penerima Bantuan Sosial Berbasis Aplikasi Desktop - Ramadhan, Azhyka Rizki; Naya, Candra; AG, Abdillah (Unversitas Muhammadiyah Riau, 2026)
The accurate distribution of social assistance remains a major challenge in improving community welfare. The process of determining eligible beneficiaries is often carried out manually, which can lead to subjectivity and inaccuracies in decision-making. Therefore, a decision support system is needed to assist the selection process by applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), enabling a more structured and objective evaluation. This study aims to implement the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method in determining the priority of social assistance recipients through a desktop-based application. The strength of TOPSIS lies in its ability to rank options based on their proximity to positive ideal solutions and to avoid negative optimal solutions. The criteria used in this study include monthly income, number of dependents, housing conditions, employment status, and productive assets. The system is developed as a desktop application equipped with features for data management, criteria weighting, and automated TOPSIS calculations to generate rankings of potential beneficiaries. The results of Black Box testing indicate that all system features function in accordance with the specified requirements, achieving a 100% success rate, thereby supporting a fast, accurate, and objective decision-making process. Therefore, this application is expected to enhance the effectiveness and transparency of social assistance distribution.